2000
DOI: 10.1523/jneurosci.20-12-04573.2000
|View full text |Cite
|
Sign up to set email alerts
|

C-Terminal Truncation of NR2A Subunits Impairs Synaptic But Not Extrasynaptic Localization of NMDA Receptors

Abstract: NMDA receptors interact via the extended intracellular C-terminal domain of the NR2 subunits with constituents of the postsynaptic density for purposes of retention, clustering, and functional regulation at central excitatory synapses. To examine the role of the C-terminal domain of NR2A in the synaptic localization and function of NR2A-containing NMDA receptors in hippocampal Schaffer collateral-CA1 pyramidal cell synapses, we analyzed mice which express NR2A only in its C-terminally truncated form. In CA1 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
132
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(145 citation statements)
references
References 40 publications
13
132
0
Order By: Relevance
“…Although this study has focused on the NR subunit, it is likely that efficient assembly and trafficking of NMDA receptors through the secretory pathway will depend on additional as yet unidentified domains in both NR1 and NR2. Indeed, C-terminal domains of NR2 are required for efficient synaptic targeting of NMDA receptors (Mori et al, 1998;Sprengel et al, 1998;Steigerwald et al, 2000), and N-terminal extracellular regions are required for efficient assembly and ER exit of AMPA receptor subunits (Leuschner and Hoch, 1999).…”
Section: The Rxr Motif: a Growing Family Of Er Retention/retrieval Simentioning
confidence: 99%
“…Although this study has focused on the NR subunit, it is likely that efficient assembly and trafficking of NMDA receptors through the secretory pathway will depend on additional as yet unidentified domains in both NR1 and NR2. Indeed, C-terminal domains of NR2 are required for efficient synaptic targeting of NMDA receptors (Mori et al, 1998;Sprengel et al, 1998;Steigerwald et al, 2000), and N-terminal extracellular regions are required for efficient assembly and ER exit of AMPA receptor subunits (Leuschner and Hoch, 1999).…”
Section: The Rxr Motif: a Growing Family Of Er Retention/retrieval Simentioning
confidence: 99%
“…Synaptic anchoring of the NMDA receptor does not require actin filaments or microtubules (Allison et al, 2000) but presumably requires binding of NMDA receptor subunits to other postsynaptic density proteins. Analysis of neurons from mice bearing NR2 genes with C-terminal truncations indicates that the C-terminal domains of NR2A and NR2B contribute to synaptic localization along with additional, as yet unidentified, domains of the receptor (Mori et al, 1998;Steigerwald et al, 2000). Candidate anchoring proteins include the PDZ domain proteins PSD-95, chapsyn-110/PSD-93, SAP102, and S-SCAM (Kornau et al, 1997;Hirao et al, 1998), the actin-binding proteins ␣-actin and spectrin (Wyszynski et al, 1997;Wechsler and Teichberg, 1998), and the AKAP yotiao (Westphal et al, 1999).…”
Section: Mechanisms Of Activity-regulated Synaptic Targeting Of Nmda mentioning
confidence: 99%
“…In vitro and fewer in vivo preparations have been used to demonstrate that NMDA receptors, too, are removed from or inserted into synaptic membrane (Rao and Craig, 1997;Liao et al, 1999;Quinlan et al, 1999;Heynen et al, 2000;Barria and Malinow, 2002;Grosshans et al, 2002;Tovar and Westbrook, 2002). However, since nearly all of these studies have used neonatal tissues, whether or not such dynamic properties of NMDA receptor subunits persist at mature synapses, in vivo, is a topic that remains relatively unexplored.Among the NMDA receptor subunits, the NR1 is necessary for NMDA receptor function, but the NR2 subunits may be relatively more central in determining NMDA receptor localization (Mori et al, 1998;Steigerwald et al, 2000;Mohrmann et al, 2002) because their C-termini are longer and permit interaction with postsynaptic density (PSD) scaffolding proteins, such as PSD-95 (Niethammer et al, 1996;Bassand et al, 1999;Sheng and Pak, 2000). Among the NR2 subunits, the NR2A and NR2B subtypes are the most prevalent in the cerebral cortex (Watanabe et al, 1992), and of the two, the NR2B subunits are shown to be particularly influential in learning and memory (Tang et al, 1999;Tang and Schuman, 2002) as they prolong NMDA receptor currents, thus allowing greater Ca influx (Mori and Mishina, 1995;Dingledine et al, 1999).…”
mentioning
confidence: 99%
“…Among the NMDA receptor subunits, the NR1 is necessary for NMDA receptor function, but the NR2 subunits may be relatively more central in determining NMDA receptor localization (Mori et al, 1998;Steigerwald et al, 2000;Mohrmann et al, 2002) because their C-termini are longer and permit interaction with postsynaptic density (PSD) scaffolding proteins, such as PSD-95 (Niethammer et al, 1996;Bassand et al, 1999;Sheng and Pak, 2000). Among the NR2 subunits, the NR2A and NR2B subtypes are the most prevalent in the cerebral cortex (Watanabe et al, 1992), and of the two, the NR2B subunits are shown to be particularly influential in learning and memory (Tang et al, 1999;Tang and Schuman, 2002) as they prolong NMDA receptor currents, thus allowing greater Ca influx (Mori and Mishina, 1995;Dingledine et al, 1999).…”
mentioning
confidence: 99%